2011
DOI: 10.1175/2010mwr3582.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dropwindsonde Observations on Typhoon Track Forecasts in DOTSTAR and T-PARC

Abstract: The typhoon surveillance program Dropwindsonde Observations for Typhoon Surveillance near the Taiwan Region (DOTSTAR) has been conducted since 2003 to obtain dropwindsonde observations around tropical cyclones near Taiwan. In addition, an international field project The Observing System Research and Predictability Experiment (THORPEX) Pacific Asian Regional Campaign (T-PARC) in which dropwindsonde observations were obtained by both surveillance and reconnaissance flights was conducted in summer 2008 in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
58
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 24 publications
5
58
0
Order By: Relevance
“…However, the WSR program has been cancelled recently due to minimal impact in recent years, perhaps because of other improvements in the data assimilation systems (Hamill et al 2013). The impact of dropsonde data on typhoon-track forecasts has been also studied extensively (e.g., Wu et al 2007;Chou et al 2011;Wu et al 2012). For example, the typhoon-track forecast error in four numerical weather prediction models was reduced by 20%-40% consistently as a result of dropsonde data collected during The Observing System Research and Predictability Experiment (THORPEX) Pacific Asian Regional Campaign (T-PARC) in 2008 .…”
mentioning
confidence: 99%
“…However, the WSR program has been cancelled recently due to minimal impact in recent years, perhaps because of other improvements in the data assimilation systems (Hamill et al 2013). The impact of dropsonde data on typhoon-track forecasts has been also studied extensively (e.g., Wu et al 2007;Chou et al 2011;Wu et al 2012). For example, the typhoon-track forecast error in four numerical weather prediction models was reduced by 20%-40% consistently as a result of dropsonde data collected during The Observing System Research and Predictability Experiment (THORPEX) Pacific Asian Regional Campaign (T-PARC) in 2008 .…”
mentioning
confidence: 99%
“…We note that many studies were made to highlight the impact of the T-PARC dropsondes for typhoon prediction (Aberson, 2003(Aberson, , 2011Wu et al, 2007;Harnisch and Weissmann, 2010;Chou et al, 2011;Weissmann et al, 2011;Kunii et al, 2012). Weissmann et al (2011) compared the results of assimilating the dropsonde data during the T-PARC period with four different models (ECMWF, JMA, NCEP and WRF).…”
Section: Introductionmentioning
confidence: 99%
“…Weissmann et al (2011) compared the results of assimilating the dropsonde data during the T-PARC period with four different models (ECMWF, JMA, NCEP and WRF). Chou et al (2011) evaluated the improvement on the TC track forecast derived by assimilating the dropsonde data in the DOTSTAR and T-PARC projects with the NCEP global forecast system (GFS). Both studies have shown that after assimilating the dropsonde data, the TC track forecast could be significantly improved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations